A tárolási feltételek hatása a kukorica Fusarium fertőzöttségére és toxin szennyezettségére - Veres, Edina; Borbély, Mária; Győri, Zoltán; Kátai, János (Acta Agraria Debreceniensis, 2002)
Corn samples harvested in 1997, 1998 and 1999 from different soil types were stored at different conditions (temperature, moisture content, state of kernels) for six months. The Fusarium contamination was examined by plate dilution method and the amount of mycotoxins (F-2, T-2, HT-2, DON, DAS) were determined applying HPLC method immediately after harvesting and in the third and sixth month of storage. The aim of our study was to find correlation between the ecological factors, storage conditions and the examined parameters mentioned above, as well as to prove them statistically. According to the examinations carried out after harvesting we could state that the soil type had no effect on the parameters. Analysing the effect of the years we found considerable differences. The Fusarium infection of corn samples in 1998, while the toxin contamination in 1999 was the highest. The results of storage experiment show that year (number of microscopic fungi, F-2, T-2, HT-2, DAS and total toxin content) and moisture content of kernels (F-2, T-2, and total toxin content) have a significant effect on the examined parameters. We could prove the effect of temperature on the T-2 content (samples with natural moisture content) and DON content (samples with 14% moisture content). Higher values were found at higher temperature storage. The ratio of damaged kernels influenced the DON concentration in the non- wetted samples and the number of microscopic fungi in the wetted samples.